2020
DOI: 10.3897/jhr.78.55762
|View full text |Cite
|
Sign up to set email alerts
|

Phoretic copulation in the velvet ant Sphaeropthalma pensylvanica (Lepeletier) (Hymenoptera, Mutillidae): A novel behavior for Sphaeropthalminae with a synthesis of mating strategies in Mutillidae

Abstract: Phoretic copulation, a form of phoresy in which a male physically transports a female by flight and/or foot from their initial site of contact before mating, is newly recorded in the Nearctic velvet ant Sphaeropthalma pensylvanica (Lepeletier, 1845) (Hymenoptera: Mutillidae). Further, this is the first record of the behavior in the species-rich subfamily Sphaeropthalminae. A description of the S. pensylvanica mating observation and photographs are provided. All published observations of copulation events in Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Neotrogaspidia species meet the size prerequisite for phoretic copulation with males being larger than females (Evans 1969;Deyrup & Manley 1986;Waldren et al 2020). The body length of N. pustulata examined here, 7.53-16.7 (11.5 AE 1.39) mm for males and 4.17-9.94 (7.28 AE 1.21) mm for females (n = 122♂130♀), suggests utilization of multiple host species with variable body size and size-dependent sex allocation (Pitts et al 2010a).…”
Section: Phoretic Copulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Neotrogaspidia species meet the size prerequisite for phoretic copulation with males being larger than females (Evans 1969;Deyrup & Manley 1986;Waldren et al 2020). The body length of N. pustulata examined here, 7.53-16.7 (11.5 AE 1.39) mm for males and 4.17-9.94 (7.28 AE 1.21) mm for females (n = 122♂130♀), suggests utilization of multiple host species with variable body size and size-dependent sex allocation (Pitts et al 2010a).…”
Section: Phoretic Copulationmentioning
confidence: 99%
“…The mating biology, habitats and hosts have been largely unknown for Neotrogaspidia, even though N. pustulata is one of the most commonly encountered mutillids in Japan. Observations by Japanese entomologists revealed that this species practices mandibular phoretic copulation (Waldren et al 2020). The Neotrogaspidia males have the morphological traits associated with prolonged phoretic copulation, like the concaved clypeus and the baso-ventral mandibular tooth (Crèvecoeur 1930;Sheldon 1970).…”
Section: Phoretic Copulationmentioning
confidence: 99%
See 3 more Smart Citations